Análise das transações na cadeia produtiva do leite em Goiás sob a ótica da Nova Economia Institucional - Rosa, Glaicon Mendes (2023)
This dissertation aimed to analyze the factors that influence the transactions in the milk production chain in Goiás. To achieve this goal, the qualitative field research was conducted with the agents of the production chain, allowing an analysis of the transactional attributes present in the relations between industries, producers and other agents. The research uses the theory of the New Institutional Economics (NEI) at its analytical level, the Economics of Transaction Costs (ECT), to analyze the transactions and reach the current governance structure. The results of the research show that the form of coordination of institutional relations in the milk production chain in Goiás is consolidated from institutionalized practices, with certain industries, producers/suppliers, customers practicing the use of production/supply contracts in specific cases, even with several market relations and contracts not formalized. However, the contracts between the parties are intrinsically incomplete, which does not make it economically feasible to specify clauses for all possible contingencies due to the limited rationality and opportunism existing in the relations. In addition, price mechanisms have flaws in their structures in the production chain, which changes the way agents behave and, consequently, their actions in the economic field, according to the configuration of hybrid structure transactions. The importance of this research lies in the understanding of the factors that influence the transactions in the which may contribute to the development of public policies and business strategies aimed at promoting sustainable growth of dairy cattle in the region.